1993
DOI: 10.1002/1097-0142(19930315)71:6<2027::aid-cncr2820710617>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal interferon in the management of malignant ascites

Abstract: Background. Ascites secondary to malignancy is a major cause of recurring morbidity in patients with ovarian cancer. In patients previously treated with cisplatin, other chemotherapeutic agents are not likely to be effective in relieving symptoms. Methods. A pilot group of ten patients was treated with intraperitoneal alpha‐2B‐interferon (α‐2B‐IFN) in an effort to provide symptomatic relief of their ascites. All patients had advanced epithelial ovarian cancer at the time of therapy and were receiving treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Diuretics have demonstrated to achieve high response rates in particular subsets of oncology patients, although their efficacy in women with peritoneal carcinomatosis has been questioned [4]. Intraperitoneal administration of Interferonalpha 2b has been attempted by a series of authors with complete response rates ranging from 10% to 30% [5][6][7]. This treatment requires frequent repeated administrations [7] and is associated with nausea, dyspepsia, abdominal distension and flu like symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Diuretics have demonstrated to achieve high response rates in particular subsets of oncology patients, although their efficacy in women with peritoneal carcinomatosis has been questioned [4]. Intraperitoneal administration of Interferonalpha 2b has been attempted by a series of authors with complete response rates ranging from 10% to 30% [5][6][7]. This treatment requires frequent repeated administrations [7] and is associated with nausea, dyspepsia, abdominal distension and flu like symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…application, including radioisotopes, radio-labeled monoclonal antibodies 15,16 and biological response modifiers (e.g., IFN-a, IFN-b, IL-2, TNF-a). [17][18][19][20] In these studies a reduction of ascites accumulation was achieved in 30-80% of patients, which was generally of short duration. These reports collectively demonstrated that there was no clear guideline for palliative treatment of symptomatic ascites, indicating the essential need for a new effective treatment strategy.…”
mentioning
confidence: 98%
“…Current therapies include diuretics, frequent large-volume paracentesis, i.p. or systemic chemotherapy, and a variety of other experimental strategies such as radiolabeled antibodies and immunostimulants (16,17). None of these approaches have been established as standard therapy for refractory malignant ascites because of limited efficacy or severe side effects (15,18).…”
mentioning
confidence: 99%